Factors Affecting Acceptance of the Use of Open Learning with the Theory of Planned Behavior (TPB) Approach to Accounting Students at Muhammadiyah University of Pekajangan Pekalongan - Khoirul Fatah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The This study aims to analyze the acceptance and use of Open Learning by using the Theory of Planned Behavior (TPB) approach to accounting students at Muhammadiyah University of Pekajangan Pekalongan who have programmed the 2020/2021 academic year. This research is classified as explanatory research with a quantitative approach. The data obtained in the form of primary data obtained directly on the object of research by submitting a questionnaire through personal chat either through social media or e-mail. Then, respondents access and fill out the online questionnaire through the questionnaire link that has been provided. The data analysis method used in this study is Structural Equation Modeling (SEM) using the Warp PLS test version 7.0.